Hak Cipta Dance Challenge Yang Diunggah Ke Aplikasi TikTok - M. Febry Saputra (Jurnal Penegakan Hukum Indonesia, 2021)
The problems studied in this research are to find out, first, how the legal protection system for Dance Challenge video owners uploaded to the TikTok application. Second, how to prove Copyright owner for Dance Challenge video uploaders on the TikTok application. The method used in this paper is the normativelegal research, which is literature law research which refers to the legal norms contained in statutory regulations by examining problems using literature either law, doctrine,or books and using the method of statutory approach. The results of the study conclude that users who create Dance Challenge video content on the TikTok application are seen as creators and have been protected as copyright holders for their cinematographic works, adhering to Law Number 28 of 2014 concerning Copyright. If the Dance Challenge video content on the TikTok application is uploaded by another party with the intention of commercial use without the rights and / or permission of the creator or copyright holder, the perpetrator can be charged with criminal penalties as regulated in Law Number 28 of 2014 concerning Copyright. There is nothing different in the process, the procedure for filing acopyright infringement lawsuit related to the Dance Challenge video on the TikTok application, whether it has been registered at the Directorate General of Intellectual Property Rights or that has not been registered and resolved through Arbitration or Commercial Court.